The study of job performance among employees in Telekom Malaysia Berhad Kuantan / Nor Umairah Mohammad Khadri and Nurazila Arshad - Mohammad Khadri, Nor Umairah; Arshad, Nurazila (Faculty of Business and Management, 2013)
This research studies the factors that affect the job performance of employees in Telekom Malaysia Berhad Kuantan. It attempts to identify the significant determinant that gives impact on employees’ performance. By constructing a hypothetical research model to investigate the effect of four variables which are motivation, pay, co-worker and promotion (independent variables) towards employees’ job performance (dependent variable),questionnaires were distributed was distributed to employees in various departments. Data was obtained and subjected to reliability tests using Cronbach’s Alpha, and the four hypotheses drawn up from the research model were subjected to test of significance correlation relationship. Out of the four hypotheses, it was found out that pay and co-worker give significant impact on employees’ job performance. Although it is not an exhaustive conclusion, this finding holds an extensive implication in the company and for future research.